(untitled) (World Bulletin of Public Health, 2024)
The authors pay special attention to the fact that in chronic purulent epitympanitis, bone tissue is involved in the inflammatory process, and chronic purulent-destructive changes occur in the cells of the mastoid process. Bone osteomyelitis leads to local and intracranial complications. Therefore, during sanitizing operations of the middle ear in epitympanitis, it is necessary to radically remove all foci of destructively altered structures of the middle ear system with exposure of the dura mater of the middle and posterior cranial fossae. The postoperative period of patient management should be aimed at intensive care